2012
DOI: 10.4283/jmag.2012.17.4.302
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Sensor-Based Detection of Picoliter Volumes of Magnetic Nanoparticle Droplets in a Microfluidic Chip

Abstract: We have designed, fabricated and tested an integrated microfluidic chip with a Planar Hall Effect (PHE) sensor. The sensor was constructed by sequentially sputtering Ta/NiFe/Cu/NiFe/IrMn/Ta onto glass. The microfluidic channel was fabricated with poly(dimethylsiloxane) (PDMS) using soft lithography. Magnetic nanoparticles suspended in hexadecane were used as ferrofluid, of which the saturation magnetisation was 3.4 emu/cc. Droplets of ferrofluid were generated in a T-junction of a microfluidic channel after hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In addition, the microfluidic system provides systematic positioning of single beads on the PHE sensor. Microfluidic valves, pumps, and mixers can be added to the microfluidic system with the PHE sensor, which can provide an automated and complex analytical device [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the microfluidic system provides systematic positioning of single beads on the PHE sensor. Microfluidic valves, pumps, and mixers can be added to the microfluidic system with the PHE sensor, which can provide an automated and complex analytical device [11].…”
Section: Introductionmentioning
confidence: 99%
“…The GMR sensor is a proximity sensor, and only local magnetic stray fields from the droplet are detected. Both simulations and experimental results (Pekas et al 2004 ; Jeong et al 2012 ; Lin et al 2013 ) have shown that magnetic stray fields concentrate at two ends of the droplet as reflected by the local maximums and minimums near the rising and falling edges of the measured signals (Fig. 1 c-bottom panel).…”
Section: Resultsmentioning
confidence: 84%
“…The RKKY interaction between two FM layer is known to cause a unidirectional magnetic anisotropy when one of the FM layers is pinned by an AF layer. Thus, the other almost free FM layer can be used as sensing layer for PHE sensors [110,[173][174][175][176][177]. The RKKY interaction can also be used to tune the H ex of the NiFe sensing layer by varying the thickness of a spacer layer or varying the thickness of FM layers.…”
Section: Spin-valvesmentioning
confidence: 99%